A randomized, controlled, first-in-patient trial of choriogonadotropin beta added to follitropin delta in women undergoing ovarian stimulation in a long GnRH agonist protocol. Issue 6 (22nd April 2022) - Fernández Sánchez, Manuel; Višnová, Hana; Larsson, Per; Yding Andersen, Claus; Filicori, Marco; Blockeel, Christophe; Pinborg, Anja; Khalaf, Yacoub; Mannaerts, Bernadette; ,
Abstract: STUDY QUESTION: Does addition of choriogonadotropin beta (recombinant CG beta) to follitropin delta increase the number of good-quality blastocysts following ovarian stimulation in a long GnRH agonist protocol? SUMMARY ANSWER: At the doses investigated, the addition of CG beta reduced the number of intermediate follicles and related down-stream parameters including the number of oocytes and blastocysts. WHAT IS KNOWN ALREADY: CG beta is a novel recombinant hCG (rhCG) molecule expressed by a human cell line (PER.C6 ® ) and has a different glycosylation profile compared to urinary hCG or rhCG derived from a Chinese Hamster Ovary (CHO) cell line. In the first-in-human trial, the CG beta pharmacokinetics were similar between men and women. In women, the AUC and the peak serum concentration (Cmax ) increased approximately dose proportionally following single and multiple daily doses. In men, a single dose of CG beta provided higher exposure with a longer half-life and proportionately higher testosterone production than CHO cell-derived rhCG. STUDY DESIGN, SIZE, DURATION: This placebo-controlled, double-blind, randomized trial (RAINBOW) was conducted in five European countries to explore the efficacy and safety of CG beta as add-on treatment to follitropin delta in women undergoing ovarian stimulation in a long GnRH agonist protocol. Randomization was stratified by centre and age (30–37 and 38–42 years). The primary endpoint was the number of good-quality blastocysts (Grade 3 BB or higher). Subjects were randomized to receive either placebo or 1, 2, 4, 8 or 12 µg CG beta added to the daily individualized follitropin delta dose during ovarian stimulation. PARTICIPANTS/MATERIALS, SETTING, METHODS: In total, 620 women (30–42 years) with anti-Müllerian hormone (AMH) levels between 5 and 35 pmol/l were randomized in equal proportions to the six treatment groups and 619 subjects started treatment. All 619 subjects were treated with an individualized dose of follitropin delta determined based on AMH (Elecsys AMH Plus Immunoassay) and body weight. Triggering with rhCG was performed when 3 follicles were ≥17 mm but no more than 25 follicles ≥12 mm were reached. MAIN RESULTS AND THE ROLE OF CHANCE: The demographic characteristics were comparable between the six treatment groups and the overall mean age, body weight and AMH were 35.6 ± 3.3 years, 65.3 ± 10.7 kg and 15.3 ± 7.0 pmol/l, respectively. The incidence of cycle cancellation (range 0–2.9%), total follitropin delta dose (mean 112 µg) and duration of stimulation (mean 10 days) were similar across the groups. At stimulation Day 6, the number and size of follicles was similar between the treatment groups, whereas at the end-of-stimulation dose-related decrease of the intermediate follicles between 12 and 17 mm was observed in comparison to the placebo group. In contrast, the number of follicles ≥17 mm was similar between the CG beta dose groups and the placebo group. A reduced number of intermediate follicles (12 to 17 mm) and fewer oocytes (mean range 9.7 to 11.2) were observed for all doses of CG beta compared to the follitropin delta only group (mean 12.5). The mean number of good-quality blastocysts was 3.3 in the follitropin delta group and ranged between 2.1 and 3.0 across the CG beta groups. The incidence of transfer cancellation was higher in the 4, 8 and 12 µg group, mostly as no blastocyst was available for transfer. In the group receiving only follitropin delta, the ongoing pregnancy rate (10–11 weeks after transfer) was 43% per started cycle versus 28–39% in CG beta groups and 49% per transfer versus 38–50% in the CG beta groups. There was no apparent effect of CG beta on the incidence of adverse events, which was 48.1% in the placebo group and 39.6–52.3% in the CG beta dose groups. In line with the number of collected oocytes, the overall ovarian hyperstimulation syndrome incidence remained lower following follitropin delta with CG beta (2.0–10.3%) compared with follitropin delta only treatment (11.5%). Regardless of the dose, CG beta was safe and well-tolerated with low risk of immunogenicity. LIMITATIONS, REASONS FOR CAUTION: The effect of the unique glycosylation of CG beta and its associated potency implications in women were not known prior to this trial. Further studies will be needed to evaluate optimal doses of CG beta for this and/or different indications. WIDER IMPLICATIONS OF THE FINDINGS: The high ongoing pregnancy rate in the follitropin delta group supports the use of individualized follitropin delta dosing in a long GnRH agonist protocol. The addition of CG beta reduced the presence of intermediate follicles with the investigated doses and negatively affected all down-stream parameters. Further clinical research will be needed to assess the optimal dose of CG beta in the optimal ratio to follitropin delta to develop this novel combination product containing both FSH and LH activity for ovarian stimulation. STUDY FUNDING/COMPETING INTEREST(S): The study was funded by Ferring Pharmaceuticals, Copenhagen, Denmark. B.M. and P.L. are employees of Ferring Pharmaceuticals. M.F.S., H.V., C.Y.A., M.F., C.B., A.P. and Y.K. have received institutional clinical trial fees from Ferring Pharmaceuticals. C.B. has received payments for lectures from Organon, Ferring Pharmaceuticals, Merck A/S and Abbott. M.F.S. has received payment for lectures from Ferring Pharmaceuticals. Y.K. has received payment for lectures from Merck and travel support from Gedeon Richter. H.V. has received consulting fees from Oxo and Obseva and travel support from Gedeon Richter, Ferring Pharmaceuticals and Merck. C.Y.A. has received payment for lectures from IBSA, Switzerland. M.F and C.Y.A. were reimbursed as members of the Data Monitoring Board in this trial. M.F. has an issued patent about unitary combination of FSH and hCG (EP1633389). TRIAL REGISTRATION NUMBER: 2017-003810-13 (EudraCT Number) TRIAL REGISTRATION DATE: 21 May 2018 DATE OF FIRST PATIENT'S ENROLMENT: 13 June 2018